Permasalahan Sosial Yang Dapat Merugikan Peserta Didik - Pratama, Bima Aditiya; Pasiska, Pasiska; Ertati, Ertati; Ngimadudin, Ngimadudin (El-Ghiroh : Jurnal Studi Keislaman, 2022)
Students from poor backgrounds, are in an environment of financial condition that is not too involved with education because there are alternative desires that are prioritized. A foggy perspective on children's schools and problems in the family due to financial problems also hinder the development and improvement of children so that their learning outcomes are low. The absence of the capacity and interest of young people to attend classes, the conditions in which the youth live, the community's views on training, customs and definite lessons. One of the works made to conquer the problem of students who experience social barriers is to offer types of social assistance and social security